2016
DOI: 10.1242/dev.140962
|View full text |Cite
|
Sign up to set email alerts
|

The functions of long noncoding RNAs in development and stem cells

Abstract: Eukaryotic genomes are pervasively transcribed, with tens of thousands of RNAs emanating from uni-and bi-directional promoters and from active enhancers. In vertebrates, thousands of loci in each species produce a class of transcripts called long noncoding RNAs (lncRNAs) that are typically expressed at low levels and do not appear to give rise to functional proteins. Substantial numbers of lncRNAs are expressed at specific stages of embryonic development, in many cases from regions flanking key developmental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
145
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 139 publications
(185 reference statements)
0
145
0
Order By: Relevance
“…Moreover, lncRNAs have been identified as new modulators in the origination and progression of glioma [6]. Mounting evidence has also demonstrated that lncRNAs involved in the regulation of gene expression in stem cell biology and in tumorigenesis [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lncRNAs have been identified as new modulators in the origination and progression of glioma [6]. Mounting evidence has also demonstrated that lncRNAs involved in the regulation of gene expression in stem cell biology and in tumorigenesis [7]. …”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are very abundant with estimates of 430 000 lncRNAs transcripts in the human genome. [71][72][73][74][75][76][77] One group of investigators estimated that there were close to 60 000 lncRNAs including 8000 oncologic lncRNAs. 74 A growing number of these lncRNAs are being isolated and characterized from thyroid and other cancers.…”
Section: Non-coding Rnas and Emt Micrornas And Emtmentioning
confidence: 99%
“…They have critical roles in several cellular processes, including gene expression regulation, chromatin remodeling, post-transcriptional regulation, and translational control. 3 The discovery of lncRNAs has dramatically altered the understanding of cell biology, especially the biology of diseases such as cancer. The identity, function, and dysregulation of lncRNAs as the leading edge of cancer research are only beginning to be understood, and recent data suggest that they may serve as important regulators of different pathways in cancer cells.…”
Section: Introductionmentioning
confidence: 99%